Local competition, innovation, and firms' bank relationships - Maximilian Zurek (Journal of Banking and Financial Economics (JBFE), 2019)
With firms searching for secured external funding by engaging in multiple bank relationships on the one hand and banks for profit maximization on the other hand, conflicts of interests may arise when firms' banks demand access to corporate private information. This information can help banks to gauge the creditworthiness of borrowers, but also exposes the latter to losses of secrecy. Thus, firms which are dependant on informative secrecy - especially innovative firms - might incur difficulties when trying to get access to external funding. As rival firms prevail within firms' own industries, a special focus is on effects of local industry specialization and competition when investigating the quantity of firms' bank connections. Analysing German firm level and county specific industry data, I find evidence that the number of bank relationships decreases for the cross-section of firms with local industry diversification. The effects of the indicators of industry-specific and overall competition are twofold with the former being positively related to the probability of using multi-bank relationships and the latter negative. Concluding, firms located in industrially specialized areas might rather refrain from relationship lending, due to potential loss of external funding, while innovative firms seem to rely on transaction-based banking. Contrarily, firms located in areas that are diversified w.r.t. industries, firm sizes and corporate landscape engage in relationship banking.
Keywords: G32; O16; R11; R51; G21; 330; Local Specialization; Firm financing; Innovation; Competition; Tacit Knowledge